2018
DOI: 10.1136/neurintsurg-2018-013928
|View full text |Cite
|
Sign up to set email alerts
|

Transient in-stent stenosis at mid-term angiographic follow-up in patients treated with SILK flow diverter stents: incidence, clinical significance and long-term follow-up

Abstract: Transient ISS after FD deployment is a common asymptomatic finding on mid-term angiographic follow-up. Complete resolution or improvement at long-term follow-up is seen in most patients who are maintained on dual antiplatelet therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Long-term clinically significant predictors for in-stent stenosis of FDS have previously been evaluated. 12,[18][19][20][21][22] Bescke et al reported one of the highest prevalence of in-stent stenosis in their cohort with 93.4% of the patients having mild stenosis. 17 observed that 40 to 50% of the patients in their cohorts had in-stent stenosis resolution in their long-term angiographic follow-up, and in both cohorts all patients remained asymptomatic from in-stent stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term clinically significant predictors for in-stent stenosis of FDS have previously been evaluated. 12,[18][19][20][21][22] Bescke et al reported one of the highest prevalence of in-stent stenosis in their cohort with 93.4% of the patients having mild stenosis. 17 observed that 40 to 50% of the patients in their cohorts had in-stent stenosis resolution in their long-term angiographic follow-up, and in both cohorts all patients remained asymptomatic from in-stent stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…This is a small sample size and longterm clinical outcomes are necessary for evaluating long-term safety and efficacy. Angiographic findings, such as evaluation of in-stent stenosis 27 or delayed parent artery occlusions, 28 need to be compared with previous generations. The sample did not include a significant number of giant aneurysms, where complex maneuvers are required, including telescoping devices in tortuous anatomies.…”
Section: Discussionmentioning
confidence: 99%
“…In a single center study John et al 2 depicted intra-stent tissue growth in 41% of cases using PED, whereas with the SILK stent Essbaiheen et al 16 reported a 44% rate and Lubicz et al 17 up to 57%.…”
Section: Discussionmentioning
confidence: 99%